2023
DOI: 10.1021/acs.jcim.3c00514
|View full text |Cite
|
Sign up to set email alerts
|

Combining SILCS and Artificial Intelligence for High-Throughput Prediction of the Passive Permeability of Drug Molecules

Poonam Pandey,
Alexander D. MacKerell

Abstract: Membrane permeability of drug molecules plays a significant role in the development of new therapeutic agents. Accordingly, methods to predict the passive permeability of drug candidates during a medicinal chemistry campaign offer the potential to accelerate the drug design process. In this work, we combine the physics-based site identification by ligand competitive saturation (SILCS) method and data-driven artificial intelligence (AI) to create a high-throughput predictive model for the passive permeability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 92 publications
1
9
0
Order By: Relevance
“…The choice of US sampling windows to be used for training the models was important, as the best results were obtained from nearly equally spaced windows, including the bounds of the windows at 0 and 30, but sampling more windows representing regions around the headgroup/water and headgroup/core interfaces. This observation is in agreement with previous work where restraint centers around these regions were determined to be the most important features for predicting the passive permeability of drug molecules …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The choice of US sampling windows to be used for training the models was important, as the best results were obtained from nearly equally spaced windows, including the bounds of the windows at 0 and 30, but sampling more windows representing regions around the headgroup/water and headgroup/core interfaces. This observation is in agreement with previous work where restraint centers around these regions were determined to be the most important features for predicting the passive permeability of drug molecules …”
Section: Discussionsupporting
confidence: 93%
“…While limitations have already been described that make it challenging to calculate absolute membrane permeability, various methods have been developed to make such predictions. These include modeling based on experimental in vitro data, implicit membrane combined with machine learning, MD simulation, and machine learning . A major limitation of most of these methods has been the lack of atomistic data, making it difficult to predict the absolute permeability and the underlying free energy surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach allows for assessment of GFE scores of individual classified atoms within the ligand that may be summed yielding the LGFE score that represents the ligand binding affinity. ,,, Notably, it has been shown that ligand ranking using the SILCS methodology is comparable with the FEP approaches while offering an improvement in computational speed of over 2 orders of magnitude. In addition, SILCS-MC has been used in conjunction with FragMaps for lipid bilayers to calculate the free energy profiles of ligands across the bilayers, information subsequently used in conjunction with a deep neural net to develop an artificial intelligence tool for prediction of ligand passive permeability. …”
Section: Introductionmentioning
confidence: 99%
“…SILCS-MC has been successfully applied in a number of studies and is computationally efficient, , requiring minutes on a single CPU core for full docking of a ligand . However, the algorithm requires multiple SILCS-MC runs to obtain adequate convergence defined as 0.5 kcal/mol in the context of the LGFE.…”
Section: Introductionmentioning
confidence: 99%